Primary neonatal sacrococcygeal neuroblastoma masquerading as a teratoma: A case report - Edan, Obay A; Jawhar, Nazar MT (Journal of Neonatal Surgery, 2022)
Background: Neonatal tumors comprise about 2% of all pediatric malignancies, with neuroblastoma having the highest incidence. Neuroblastoma involving the adrenal medulla and sympathetic ganglia is the most typical scenario in infancy, while the pelvic variant is rare. We report this case because of the unusual and rare presentation of neuroblastoma in a newborn baby mimicking sacrococcygeal teratoma. Case Presentation: A newborn male baby presented with a firm sacral mass, about 5 x 7 cm, with normal overlying skin. MRI revealed an intrapelvic mass extending to the sacral region encasing the coccyx. After preparation, complete tumor excision was performed, and the diagnosis of neuroblastoma was confirmed by histological and immunohistochemical study. Conclusion: Primary neonatal neuroblastoma presenting as a sacrococcygeal mass is a rare and atypical clinical finding of neuroblastoma. It is hard to diagnose this sort of tumor preoperatively unless the mass is subjected to histological and immunohistochemical analysis after tumor excision.